Metaphor-metonymy coupling in the short story "Boys who like boys" gay culture perspective - Saez, Marco Suavillo (College of Arts and Letters, University of the Philippines Diliman, 1996)
This is a study of how metaphor-metonymy coupling evolve in a gay narrative text. By applying Floyd Merrel's model of the coupling, it is able to identify metaphor and metonymy interplay in the short story "Boys Who like Boys" by Vicente G. Groyon III. Furthermore, the identification of such interplay shows that metaphor and metonymy intersect at critical points of the story revealing a plot which is a reaction to society's construct of homosexuality. This study concludes that the metaphor-metonymy coupling theory is appropriate in "extracting" the gay attitude existing in the text.